A doped hydrogen storage nanomaterial and preparation method thereof
By performing nitrogen doping in graphene oxide materials and forming copper-iron composite nanoparticles in situ, the challenges of existing hydrogen storage materials in terms of safety, capacity and cost are solved, efficient hydrogen adsorption and release are achieved, and the comprehensive performance of hydrogen storage materials is improved.
Patent Information
- Application Number
- CN202410541033.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-30
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-04-30
AI Technical Summary
Existing hydrogen storage materials have challenges in terms of safety, capacity and cost, especially the safety of high-pressure gaseous hydrogen storage technology, solid hydrogen storage materials are costly and have low mass hydrogen storage density, low temperature liquid and organic liquid hydrogen storage processes are complex and energy consumption is high.
By using graphene oxide as the substrate material, nitrogen doping is performed to increase the specific surface area to improve the adsorption capacity of hydrogen elements, and copper-iron composite nanoparticles are formed in situ within the graphene oxide structure to form a multiple adsorption structure to improve hydrogen storage performance.
The specific surface area and adsorption volume of hydrogen storage materials are achieved, the adsorption and release capacity of hydrogen gas is enhanced, the comprehensive performance of hydrogen storage materials is improved, and the cost of hydrogen storage is reduced.
Smart Images

Figure CN118479418B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of hydrogen storage materials, and specifically refers to a doped hydrogen storage nanomaterial and a preparation method thereof. Background Art
[0002] Energy issues have long been one of the most widely concerned issues. Due to environmental pollution and the non-renewable nature of fossil energy, the development and utilization of clean energy has become a topic that must be discussed. Lithium battery energy is an energy source that can be widely used at present. Since lithium ore is a non-renewable energy source, it cannot solve the energy problem from the root. The energy provided by lithium batteries is generated by the chemical reaction between lithium ions and the positive and negative electrodes of the battery. In fact, it is the energy converted by chemical bond energy in the chemical reaction. The energy provided by hydrogen combustion comes from the redox reaction between hydrogen and oxygen. A large amount of energy is released while chemical bonds are formed and broken. The energy provided by hydrogen combustion is usually greater than that provided by lithium batteries. The calorific value provided by each kilogram of lithium battery is about 0.72MJ, while the calorific value provided by each kilogram of hydrogen can reach about 142.4MJ. More importantly, Hydrogen energy is a completely zero-emission energy source; the hydrogen energy industry chain includes upstream hydrogen production, midstream storage and transportation, downstream filling and terminal hydrogen energy application, among which midstream storage and transportation of hydrogen energy are relatively difficult; the difficulties in hydrogen storage mainly face three problems: 1. Safety issues. Hydrogen is an active gas that can cause hydrogen embrittlement reactions in hydrogen storage materials made of steel and aluminum, resulting in cracks in the wall of the gas tank, which in turn leads to hydrogen leakage; 2. Capacity issues. Hydrogen is currently stored and transported mainly in the form of high-pressure gas, which requires external materials to be able to withstand considerable pressure; 3. Cost issues. Since hydrogen storage materials need to withstand higher pressures, carbon fiber materials are currently commonly used as intermediate materials for gas tanks. Since carbon fiber materials are expensive and have low production capacity, the cost of storing and transporting hydrogen energy is high. At the same time, the quality of hydrogen transportation is lower than that of the gas tank, which increases transportation costs.
[0003] In the existing technology, the main types of hydrogen storage include high-pressure gaseous hydrogen storage, solid-state hydrogen storage, low-temperature liquid hydrogen storage and organic liquid hydrogen storage. High-pressure gaseous hydrogen storage technology is widely used, but its safety is relatively poor; solid-state hydrogen storage is widely studied, but its actual application is relatively small. Solid-state hydrogen storage mainly focuses on the research of hydrogen storage materials. The cost of hydrogen storage materials is high and the mass hydrogen storage density is low; low-temperature liquid hydrogen storage and organic liquid hydrogen storage have complex processes, high pump costs, and require ultra-low temperatures below -200°C. They consume high energy and the technology is immature. Summary of the invention
[0004] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a doped hydrogen storage nanomaterial and a preparation method thereof. The present invention uses graphene oxide as a base material, performs nitrogen doping, and improves the adsorption capacity of hydrogen by increasing the specific surface area. In situ, copper-iron composite nanoparticles are formed, and bimetallic compounds are doped in the graphene oxide structure. Multiple adsorption structures can be formed in the graphene structure, the specific surface area is increased, the adsorption volume is increased, and hydrogen can be adsorbed by chemical adsorption, thereby improving the hydrogen storage performance of the composite material.
[0005] In order to achieve the above object, the present invention also provides a method for preparing a doped hydrogen storage nanomaterial, which specifically comprises the following steps:
[0006] S1. Disperse graphene oxide in deionized water, add melamine, stir thoroughly, add 0.5-0.8 g of sodium bicarbonate, and carry out ultrasonic treatment at 400-500 W for 30-40 min to make the reaction system evenly dispersed. After sealing, raise the temperature to 150-180 ° C and react for 12-18 h. After the reaction system is cooled to room temperature, wash and dry to obtain nitrogen-doped graphene oxide;
[0007] Preferably, in step S1, the mass concentration of graphene oxide in deionized water is 1-3 g / L;
[0008] Preferably, in step S1, the mass ratio between the graphene oxide and melamine is 2-4:1;
[0009] S2, dissolving copper nitrate and ferric nitrate in deionized water, adding citric acid, stirring at 300 rpm for 20-30 min, adjusting the pH to 7.0-7.3, to obtain a copper / iron complex precursor solution;
[0010] Preferably, in step S2, the mass ratio between the copper nitrate and the iron nitrate is 1:4-5;
[0011] Preferably, in step S2, the mass concentration of the ferric nitrate in deionized water is 40-50 g / L;
[0012] Preferably, in step S2, the mass concentration of citric acid in deionized water is 15-20 g / L;
[0013] S3, dispersing the nitrogen-doped graphene oxide prepared in step S1 in deionized water, adding the copper / iron complex precursor solution prepared in step S2, mixing evenly, raising the reaction temperature to 80-90°C, continuing to stir for 10-30 minutes, and then continuing to raise the reaction temperature to 180-200°C. After reacting for 20-30 minutes, filter, remove the filtrate, wash with deionized water, and dry to obtain copper / iron composite nitrogen-doped graphene aerogel;
[0014] Preferably, in step S3, the volume ratio of the copper / iron complex precursor solution to the nitrogen-doped coastal graphene dispersion is 1-2:100;
[0015] S4, transferring the Cu / Fe-NC prepared in step S3 to a high-pressure reactor, raising the temperature to 600-800°C at 5°C / min, and keeping the temperature for 2-3h, and after the reaction system is naturally cooled to room temperature, obtaining a doped hydrogen storage nanomaterial;
[0016] The present invention also provides a doped hydrogen storage nano material prepared according to the preparation method.
[0017] The beneficial effects achieved by the present invention are as follows:
[0018] The present invention provides a doped hydrogen storage nano material and a preparation method thereof. The present invention uses graphene oxide as a base material, performs nitrogen doping, increases the specific surface area, improves the adsorption capacity of hydrogen elements, forms copper-iron composite nano particles in situ, and dopes bimetallic compounds in the graphene oxide structure, so that multiple adsorption structures can be formed in the graphene structure, the specific surface area is increased, the adsorption volume is increased, and hydrogen can be adsorbed by chemical adsorption, thereby improving the hydrogen storage performance of the composite material. The present invention adopts graphene oxide and melamine as principles, in-situ doping of N elements in the graphene oxide structure, and the graphene oxide has π bonds, which can form a three-dimensional network structure with melamine molecules through the π-π stacking effect. structure, increasing the specific surface area of graphene oxide, and the addition of sodium bicarbonate can provide a more uniform pore structure; copper nitrate and ferric nitrate are prepared into a composite precursor solution by a sol-gel method, nitrogen-doped graphene aerogel is fully contacted with the precursor solution, iron atoms and copper atoms are introduced into the graphene sheet structure, and after calcination, a doped hydrogen storage nanomaterial with a porous structure can be formed; when hydrogen is stored, the nanomaterial prepared by the present invention can absorb hydrogen through the porous structure, when the contact area between hydrogen and the nanomaterial is increased, hydrogen and copper / iron composite nanoparticles are combined with metal elements through chemical adsorption, and when dehydrogenation occurs, the metal elements are activated, which can promote the release of hydrogen energy, thereby improving the comprehensive performance of the hydrogen storage material. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1This is a TEM image of the doped hydrogen storage nanomaterial prepared in Example 1 of the present invention;
[0020] Figure 2 The hydrogen absorption result diagram of the hydrogen storage nanomaterials described in the embodiments of the present invention and the comparative examples;
[0021] Figure 3 The graph is a diagram showing the dehydrogenation results of the hydrogen storage nanomaterials described in the examples and comparative examples of the present invention.
[0022] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION
[0023] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0024] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.
[0025] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials and test strains used in the following examples are purchased from commercial channels unless otherwise specified.
[0026] Example 1
[0027] This embodiment provides a method for preparing a doped hydrogen storage nanomaterial, which specifically includes the following steps:
[0028] S1. Place 1 g of graphene oxide in 1000 mL of deionized water, stir until the graphene oxide is fully dispersed, add 0.5 g of melamine and continue stirring, add 0.5 g of sodium bicarbonate, transfer to a water bath sonicator and sonicate at 500 W for 30 min, then transfer to a high-pressure reactor, raise the reaction temperature to 150 ° C under sealed conditions, react for 16 h, wait for the reaction system to cool to room temperature, wash with anhydrous ethanol and deionized water three times respectively, and dry in a vacuum oven at 60 ° C to obtain nitrogen-doped graphene oxide;
[0029] S2. Accurately weigh 0.5 g of copper nitrate monohydrate and 2 g of ferric nitrate nonahydrate, place them in a beaker, add them to 50 mL of deionized water, stir until the copper nitrate and ferric nitrate are fully dissolved, accurately weigh 0.75 g of citric acid, add it to the reaction system, add a magnet, place it on a magnetic stirrer, stir at 300 rpm for 20 min, and adjust the pH to 7.0 with ammonia water to obtain a copper / iron complex precursor solution;
[0030] S3, dispersing the nitrogen-doped graphene oxide prepared in step S1 in 100 mL of deionized water, placing it under ultrasonic treatment at 300 W power for 10 min, adding 1 mL of the copper / iron complex precursor solution prepared in step S2, placing it on a magnetic stirrer, stirring it at 400 rpm for 20 min, and after mixing evenly, raising the reaction temperature to 80°C, continuing to stir, reacting for 20 min, raising the temperature to 180°C, reacting for 30 min, and cooling the reaction system to room temperature, filtering, removing the filtrate, washing the solid surface with deionized water, and placing it in a vacuum oven at 40°C for 24 h to obtain copper / iron composite nitrogen-doped graphene aerogel (Cu / Fe-NC);
[0031] S4. Place the Cu / Fe-NC prepared in step S3 in a high-pressure reactor, raise the temperature to 600° C. at 5° C. / min, and keep the temperature for 3 hours. After the reaction system is naturally cooled to room temperature, a doped hydrogen storage nanomaterial is obtained.
[0032] The present invention also provides a doped hydrogen storage nano material prepared according to the above preparation method.
[0033] Example 2
[0034] This embodiment provides a method for preparing a doped hydrogen storage nanomaterial, which specifically includes the following steps:
[0035] S1. Place 2 g of graphene oxide in 1000 mL of deionized water, stir until the graphene oxide is fully dispersed, add 0.5 g of melamine and continue stirring, add 0.6 g of sodium bicarbonate, transfer to a water bath sonicator and sonicate at 400 W for 30 min, then transfer to a high-pressure reactor, raise the reaction temperature to 170 ° C under sealed conditions, react for 18 h, cool the reaction system to room temperature, wash with anhydrous ethanol and deionized water three times respectively, and dry in a vacuum oven at 60 ° C to obtain nitrogen-doped graphene oxide;
[0036] S2. Accurately weigh 0.4 g of copper nitrate monohydrate and 2 g of ferric nitrate nonahydrate, place them in a beaker, add them to 40 mL of deionized water, stir until the copper nitrate and ferric nitrate are fully dissolved, accurately weigh 0.8 g of citric acid, add it to the reaction system, add a magnet, place it on a magnetic stirrer, stir at 300 rpm for 30 min, and adjust the pH to 7.3 with ammonia water to obtain a copper / iron complex precursor solution;
[0037] S3, dispersing the nitrogen-doped graphene oxide prepared in step S1 in 100 mL of deionized water, placing it under ultrasonic treatment at 300 W power for 10 min, adding 2 mL of the copper / iron complex precursor solution prepared in step S2, placing it on a magnetic stirrer, stirring it at 400 rpm for 20 min, and after mixing evenly, raising the reaction temperature to 90°C, continuing to stir, reacting for 10 min, raising the temperature to 200°C, reacting for 20 min, and cooling the reaction system to room temperature, filtering, removing the filtrate, washing the solid surface with deionized water, and placing it in a vacuum oven at 40°C for 24 h to obtain copper / iron composite nitrogen-doped graphene aerogel (Cu / Fe-NC);
[0038] S4. Place the Cu / Fe-NC prepared in step S3 in a high-pressure reactor, raise the temperature to 800° C. at 5° C. / min, and keep the temperature for 2 hours. After the reaction system is naturally cooled to room temperature, a doped hydrogen storage nanomaterial is obtained.
[0039] The present invention also provides a doped hydrogen storage nano material prepared according to the above preparation method.
[0040] Example 3
[0041] This embodiment provides a method for preparing a doped hydrogen storage nanomaterial, which specifically includes the following steps:
[0042] S1. Place 3 g of graphene oxide in 1000 mL of deionized water, stir until the graphene oxide is fully dispersed, add 1 g of melamine and continue stirring, add 0.8 g of sodium bicarbonate, transfer to a water bath sonicator and sonicate at 450 W for 40 min, then transfer to a high-pressure reactor, raise the reaction temperature to 180 ° C under sealed conditions, react for 12 h, wait for the reaction system to cool to room temperature, wash three times with anhydrous ethanol and deionized water respectively, and dry in a vacuum oven at 60 ° C to obtain nitrogen-doped graphene oxide;
[0043] S2. Accurately weigh 0.5 g of copper nitrate monohydrate and 2 g of ferric nitrate nonahydrate, place them in a beaker, add them to 50 mL of deionized water, stir until the copper nitrate and ferric nitrate are fully dissolved, accurately weigh 0.8 g of citric acid, add it to the reaction system, add a magnet, place it on a magnetic stirrer, stir at 300 rpm for 20 min, and adjust the pH to 7.2 with ammonia water to obtain a copper / iron complex precursor solution;
[0044] S3, dispersing the nitrogen-doped graphene oxide prepared in step S1 in 100 mL of deionized water, placing it under ultrasonic treatment at 300 W power for 10 min, adding 1 mL of the copper / iron complex precursor solution prepared in step S2, placing it on a magnetic stirrer, stirring it at 400 rpm for 20 min, and after mixing evenly, raising the reaction temperature to 80°C, continuing to stir, reacting for 30 min, raising the temperature to 200°C, reacting for 30 min, and cooling the reaction system to room temperature, filtering, removing the filtrate, washing the solid surface with deionized water, and drying it in a vacuum oven at 40°C for 24 h to obtain copper / iron composite nitrogen-doped graphene aerogel (Cu / Fe-NC);
[0045] S4. Place the Cu / Fe-NC prepared in step S3 in a high-pressure reactor, raise the temperature to 700° C. at 5° C. / min, and keep the temperature for 2 hours. After the reaction system is naturally cooled to room temperature, a doped hydrogen storage nanomaterial is obtained.
[0046] The present invention also provides a doped hydrogen storage nano material prepared according to the above preparation method.
[0047] Comparative Example 1
[0048] This comparative example provides a method for preparing a doped hydrogen storage nanomaterial, which differs from Example 1 only in that step S2 in the preparation method does not include ferric nitrate, and an iron-containing precursor solution is obtained through step S2. The remaining components, component content agents, and preparation method steps are the same as those in Example 1.
[0049] Comparative Example 2
[0050] This comparative example provides a method for preparing a doped hydrogen storage nanomaterial, which differs from Example 1 only in that step S2 in the preparation method does not include copper nitrate, and an iron-containing precursor solution is obtained through step S2. The remaining components, component content agents, and preparation method steps are the same as those in Example 1.
[0051] Experimental Example 1
[0052] In this experimental example, the microscopic morphology of the doped hydrogen storage nanomaterial prepared in Example 1 was observed, and the morphology of the hydrogen storage nanomaterial prepared in Example 1 was analyzed using a transmission scanning electron microscope (Tecnai G2F20). Figure 1This is a TEM image of the doped hydrogen storage nanomaterial prepared in Example 1 of the present invention. From the image, it can be seen that the graphene layer wrinkles, and copper / iron composite nanoparticles exist between the layer wrinkles.
[0053] Experimental Example 2
[0054] In this experimental example, the hydrogen storage performance of the hydrogen storage nanomaterials prepared in Examples 1-3 and Comparative Examples 1-2 was analyzed and recorded using a pressure composite temperature test device (Sieverts type). Before the test, the device system was repeatedly evacuated for multiple times, and then the nanomaterials were activated with a volume calibration sample. The activation conditions were: hydrogen pressure 2MPa, temperature 350°C, activation time 2h, and number of cycles 3 times. After the activation was completed, a hydrogen absorption test was performed at a hydrogen pressure of 2MPa and a temperature of 350°C, and a dehydrogenation test was performed at a hydrogen pressure of 0.1MPa and a temperature of 350°C.
[0055] Figure 2 This is a graph showing the hydrogen absorption results of the hydrogen storage nanomaterials described in the embodiments and comparative examples of the present invention. As shown in the figure, the hydrogen storage nanomaterials prepared in Examples 1-3 can adsorb more than 2.5 mg / g of hydrogen, and have a faster hydrogen adsorption rate; the nanomaterials described in Comparative Examples 1 and 2 are relatively poor in both adsorption amount and adsorption rate.
[0056] Figure 3 This is a graph showing the dehydrogenation results of the hydrogen storage nanomaterials described in the embodiments and comparative examples of the present invention. As shown in the figure, the hydrogen storage nanomaterials prepared in Examples 1-3 can release hydrogen quickly and in a large amount, while the nanomaterials prepared in Comparative Examples 1 and 2 release hydrogen slowly, and the hydrogen is fixed in the nanomaterials and cannot be effectively released.
[0057] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
[0058] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a doped hydrogen storage nanomaterial, characterized in that: The specific steps include: S1. Disperse graphene oxide in deionized water, add melamine, stir thoroughly, add 0.5-0.8 g of sodium bicarbonate, and carry out ultrasonic treatment at 400-500 W for 30-40 min to make the reaction system evenly dispersed. After sealing, raise the temperature to 150-180 ° C and react for 12-18 h. After the reaction system is cooled to room temperature, wash and dry to obtain nitrogen-doped graphene oxide; S2, dissolving copper nitrate and ferric nitrate in deionized water, adding citric acid, stirring at 300 rpm for 20-30 min, adjusting the pH to 7.0-7.3, to obtain a copper / iron complex precursor solution; S3, dispersing the nitrogen-doped graphene oxide prepared in step S1 in deionized water, adding the copper / iron complex precursor solution prepared in step S2, mixing evenly, raising the reaction temperature to 80-90°C, continuing to stir for 10-30 minutes, and then continuing to raise the reaction temperature to 180-200°C. After reacting for 20-30 minutes, filter, remove the filtrate, wash with deionized water, and dry to obtain copper / iron composite nitrogen-doped graphene aerogel; S4. Transfer the copper / iron composite nitrogen-doped graphene aerogel prepared in step S3 to a high-pressure reactor, increase the temperature to 600-800° C. at 5° C. / min, and keep the temperature for 2-3 hours. After the reaction system is naturally cooled to room temperature, a doped hydrogen storage nanomaterial is obtained.
2. The method for preparing a doped hydrogen storage nanomaterial according to claim 1, characterized in that: In step S1, the mass concentration of graphene oxide in deionized water is 1-3 g / L.
3. The method for preparing a doped hydrogen storage nanomaterial according to claim 2, characterized in that: In step S1, the mass ratio of graphene oxide to melamine is 2-4:
1.
4. The method for preparing a doped hydrogen storage nanomaterial according to claim 3, characterized in that: In step S2, the mass ratio between the copper nitrate and the iron nitrate is 1:4-5.
5. The method for preparing a doped hydrogen storage nanomaterial according to claim 4, characterized in that: In step S2, the mass concentration of the ferric nitrate in deionized water is 40-50 g / L.
6. The method for preparing a doped hydrogen storage nanomaterial according to claim 5, characterized in that: In step S3, the volume ratio of the copper / iron complex precursor solution to the nitrogen-doped graphene oxide dispersion is 1-2:
100.
7. A doped hydrogen storage nanomaterial, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Nitrogen mixed grapheme hydrogel or aerogel and preparation method thereof
CN102874796A
Nitrogen doped graphene material and preparation method thereof
CN105565307A